“UDL is a way of thinking”; theorizing UDL teacher knowledge, beliefs, and practices - Lambert, Rachel; McNiff, Avery; Schuck, Rachel; Imm, Kara; Zimmerman, Sara (Frontiers in Education, 2023)
Using design research methodology, we explored changes in experienced educators’ beliefs, knowledge, and practices related to Universal Design for Learning (UDL) following a professional development course for in-service teachers and teacher leaders on UDL and design thinking. Data included analysis of focus groups 9 months after the summer professional development course. Findings indicated shifts in educators’ beliefs about UDL, moving from conceptions of UDL as a static, inflexible framework to a “way of thinking” – moment-to-moment responsiveness to students’ access needs. Another finding was the importance of empathy interviews as a practice to learn about students and build relationships. Participants stressed the importance of questioning one’s own deficit thinking about students with disabilities. We call for more investigations into teacher knowledge, beliefs, and practices on UDL.